The Role Of Mitragyna speciosa (Korth) As An Anti-Inflammatory Agent In Wound Healing In Living Cells - Ferdinan Hanafi, Eka Satria Akbar; Pramesti, Rosandhy Alfiyah; Jazuli, Muhammad Aqil Siroj; Rihhadatulays, Khuzaimah Nur Juhanifah; Salim, Hotimah Masdan; Savitri, Ardyarini Dyah (Jurnal Ilmu Kesehatan dan Kesehatan, 2025)
Background: Wound is a condition in which the integrity of body tissue is disrupted, leading to the activation of a complex biological process known as wound healing. This process aims to restore the protective skin barrier, prevent infection, and minimize fluid loss. It involves sequential phases of hemostasis, inflammation, proliferation, and remodeling. While inflammation is essential for initiating repair, prolonged or excessive inflammation may delay the healing process. Mitragyna speciosa (Korth) is a medicinal plant traditionally used in various cultures and has been reported to exhibit multiple pharmacological properties, including anti-inflammatory, antioxidant, antibacterial, analgesic, and wound-healing activities. Methods: The present systematic review was conducted to identify and synthesize scientific evidence regarding the potential of Mitragyna speciosa extract as a therapeutic agent in wound healing through anti-inflammatory and other biological pathways. Literature searches were performed in ScienceDirect, PubMed, MDPI, DOAJ, and Google Scholar following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results :A total of 1,176 studies were screened, and five experimental studies fulfilled the inclusion criteria. The findings consistently demonstrated that Mitragyna speciosa extract suppressed pro-inflammatory mediators such as nitric oxide, reactive oxygen species, tumor necrosis factor-alpha, interleukin-6, and enzymatic pathways including cyclooxygenase-2 and 5-lipoxygenase. In addition, the extract stimulated cell migration, endothelial migration, and angiogenesis, thereby supporting tissue regeneration. Toxicity profiles suggest that the extract is safe at effective concentrations, although responses remain dose-dependent. Conclusions: Overall, Mitragyna speciosa shows promise as a plant-based therapeutic option for wound healing. Nevertheless, current evidence is limited and largely derived from in vitro studies, indicating the need for more extensive in vivo and clinical investigations.